iZombie. The complete third season [videorecording (DVD)] - Etheridge, Dan (Daniel Derrickson); Bloom, Jason; McIver, Rose, 1988-; Goodwin, Malcolm; Buckley, Robert, 1981- (Warner Bros. Entertainment, 2017)
When a medical resident becomes a zombie, she helps the police solve murders by working in a morgue.